Evaluation of Contamination in Milk Samples Pooled From Independently Collected Quarters Within a Laboratory Setting - Dean, Chris J.; Peña-Mosca, Felipe; Ray, Tui; Heins, Bradley J.; Machado, Vinicius S.; Pinedo, Pablo J.; Caixeta, Luciano S.; Noyes, Noelle R. (Frontiers in Veterinary Science, 2022)
The primary objective of this observational study was to evaluate the prevalence of contamination from independently collected quarter-level milk samples pooled in a laboratory and subjected to bacterial culture. To address this objective, weekly quarter-level milk samples were collected longitudinally from a cohort of 503 primiparous cows from five organic dairy farms during the first 5 weeks after calving. Individual quarter milk samples were pooled in a laboratory using aseptic technique (“lab-pooled”) and subjected to bacterial culture. In the sample set of 2,006 lab-pooled milk samples, 207 (10%) were classified as contaminated using a standard definition (i.e., growth of three or more distinct microorganisms). Subsequent culturing of corresponding quarter-level milk samples revealed that many of the contaminated lab-pooled sample results (i.e., 46.7%) were the result of intramammary infections with different pathogens across the quarters, rather than actual contamination within any single quarter (i.e., “true contamination”). The odds of true contamination were lower when the lab-pooled sample exhibited growth of three microorganisms compared to more than 3 microorganisms. Our findings suggest that pooling of quarter samples within a laboratory setting may yield lower rates of contamination compared to those previously reported from samples composited on-farm, but that current cut-offs to define contamination may need to be evaluated for use with lab-pooled samples. Further investigation of use of lab-pooled samples may be warranted to reduce costs while still providing useful scientific insight.